Bionic intestinal villus aerogel as well as preparation method and application thereof
By grafting the bionic small intestinal villus structure on the aerogel skeleton and using environmentally friendly ligands, the problem of degradation in traditional aerogel materials in moldy, loading or high-temperature environments is solved, and a bionic small intestinal villus aerogel material with efficient heat insulation, flame retardant and antibacterial bionic small intestinal villus aerogel material is achieved.
Patent Information
- Application Number
- CN202411672318.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing aerogel materials have deteriorated heat insulation and flame retardant properties in moldy, loaded or high-temperature environments, and traditional flame retardants are harmful to the environment, and the preparation process is complex and costly.
Aerogels with bionic small intestinal villus structure are used to graft the bionic villus structure on the layered structure of the aerogel framework and use environmentally friendly components such as phytic acid-polyethyleneimine ligands to form materials with low thermal conductivity and high flame retardant properties.
It achieves excellent flame retardant, antibacterial and thermal insulation properties in mold-prone, load- or high-temperature environments, reduces the production cost of materials, and simplifies the preparation process, suitable for construction, industry and aerospace fields.
Smart Images

Figure CN119505353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aerogel and a preparation method and application thereof, and in particular to a bionic intestinal villus aerogel and a preparation method and application thereof. Background Art
[0002] Thermal insulation and flame retardant materials are widely used in the fields of construction, aerospace, transportation, etc. Their performance is directly related to the safety and stability of the materials under high temperature or fire conditions. Existing thermal insulation materials are mostly based on a composite structure of inorganic and organic components, and thermal insulation properties are achieved by filling the internal pores of the material with gas with low thermal conductivity, such as aerogels, foam materials and vacuum insulation panels. In terms of flame retardant materials, flame retardants are often added to the material or the heat resistance of the material itself is enhanced to inhibit the spread of flames and heat transfer. However, these materials may be affected in terms of thermal insulation and flame retardant properties under conditions such as long-term use, prone to mold, and under pressure, making it difficult to take into account both structural strength and application life.
[0003] At present, in order to improve the performance of materials in terms of flame suppression, thermal barrier, etc., research is mainly focused on the modification of aerogel matrix structure and the addition of reinforcing phase. For example, some studies have achieved preliminary flame retardant and thermal insulation effects by using silica aerogel matrix combined with the addition of flame retardants or modified components.
[0004] Although existing aerogel materials have made significant progress in thermal insulation and flame retardant properties, they still have shortcomings under certain specific conditions, especially in terms of long-term stability, structural toughness and processing costs: ① Insufficient stability and moisture resistance: Due to the loose pore structure of most aerogels, the materials are easily affected in moldy environments, resulting in reduced thermal insulation and flame retardant properties. In addition, traditional aerogels are prone to structural collapse in high temperature environments, affecting their thermal insulation effect. ② Limited mechanical properties: Traditional silica aerogels are prone to powderization after impact or pressure due to their high brittleness, and are not suitable for use in scenarios with high loads. Although the introduction of reinforcing phases such as fibers into aerogels can improve toughness, it often affects their low-density characteristics. ③ Impact of flame retardants on the environment: Many traditional flame retardants may contain harmful substances and may produce toxic gases under high temperature conditions, which has adverse effects on the environment and health. In order to solve this problem, the research on environmentally friendly flame retardants and non-toxic aerogels has become a new research hotspot, but their performance and cost still need to be optimized. ④ Complex processing and high cost: The preparation process of aerogel involves multiple steps of chemical reactions and solvent removal. The preparation cycle is long and the cost is relatively high, which makes it difficult to meet the needs of large-scale commercialization.
[0005] The above problems mainly stem from the fact that the microstructure of aerogel is easily affected by environmental factors. At the same time, the brittleness of inorganic components, the chemical composition of traditional flame retardants and the complex preparation process all restrict its application potential. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a bionic intestinal villus structure aerogel that still maintains excellent flame retardant, antibacterial and heat insulation properties in a mold-prone, load or high temperature environment;
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned bionic intestinal villus structure aerogel;
[0008] The third object of the present invention is to provide the application of the above-mentioned bionic intestinal villus structure aerogel.
[0009] Technical solution: The bionic intestinal villus aerogel of the present invention comprises an aerogel skeleton with a layered structure, and a bionic villus structure is grafted onto the layered structure of the aerogel skeleton; the bionic intestinal villus aerogel comprises the following components by weight percentage: 1-1.5 parts of a carbon source, 1.5-2.5 parts of a cross-linking agent, 0.2-0.5 parts of a catalyst, and 0.5-1 parts of a phytic acid-polyethyleneimine ligand.
[0010] Wherein, each layer structure of the aerogel skeleton is uniformly grafted with a bionic villi structure.
[0011] The phytic acid-polyethyleneimine ligand is prepared by the following process: adjusting the aqueous solution of polyethyleneimine to be acidic, adding the phytic acid aqueous solution, stirring, generating a white precipitate, washing, freeze-drying, and obtaining the phytic acid-polyethyleneimine ligand; the mass ratio of the polyethyleneimine to the phytic acid is 1:1 to 2:1; the molecular weight of the polyethyleneimine is 70000-250000 M.W.
[0012] Wherein, the carbon source is at least one of hydroxypropyl methylcellulose, cellulose nanocrystals or cellulose nanofibers; the crosslinking agent is methyltrimethoxysilane and / or hexadecyltrimethoxysilane; and the catalyst is ammonia water and / or sodium hydroxide.
[0013] The method for preparing the bionic intestinal villus aerogel comprises the following steps:
[0014] (1) adjusting the aqueous solution of polyethyleneimine ligand to be acidic, adding phytic acid aqueous solution, stirring to generate white precipitate, washing, freeze-drying to obtain phytic acid-polyethyleneimine ligand, and grinding to obtain phytic acid-polyethyleneimine ligand powder;
[0015] (2) dissolving the carbon source, adding a cross-linking agent to hydrolyze the carbon source to form a Si-O-Si network; then adding a catalyst to cross-link the carbon source and the cross-linking agent to form a gel precursor;
[0016] (3) adding phytic acid-polyethyleneimine ligand powder to the gel precursor and stirring until the phytic acid-polyethyleneimine ligand is dissolved and dispersed in the gel precursor;
[0017] (4) Directional freeze drying is performed to obtain bionic intestinal villus aerogel.
[0018] Wherein, in step (1), the mass ratio of polyethyleneimine to phytic acid is 1:1 to 2:1.
[0019] Wherein, in step (1), the molecular weight of the polyethyleneimine is 70,000 to 250,000 M.W.
[0020] Wherein, in step (1), the aqueous solution of polyethyleneimine ligand is adjusted to a pH value of 3-4.
[0021] Wherein, in step (1), the freeze-drying time is 48 to 54°C; and the temperature is -55 to -60°C.
[0022] In step (1), polyethyleneimine is dispersed in water and stirred at high speed until the polyethyleneimine is completely dissolved and uniformly dissolved to form a polyethyleneimine aqueous solution; wherein the speed of the high-speed stirring is 800-850 r / min; after adding acetic acid to the polyethyleneimine aqueous solution to adjust the pH to 3-4, stirring at low speed is performed to complete the protonation degree; wherein the speed of the low-speed stirring is 250-300 r / min.
[0023] In step (1), phytic acid is dispersed in water to form a phytic acid aqueous solution; the phytic acid aqueous solution is added to the polyethyleneimine aqueous solution and stirred at high speed to generate a white precipitate; wherein the speed of the high-speed stirring is 800-850r / min; the white precipitate is washed with a vacuum filter, and after washing, the precipitate is preferably frozen at -20°C for 8h and then freeze-dried for 36h.
[0024] The mass of the carbon source, cross-linking agent, catalyst and phytic acid-polyethyleneimine ligand powder respectively accounts for 1-1.5%, 1.5-2.5%, 0.2-0.5% and 0.5-1% of the mass of the whole system obtained in step (3).
[0025] Among them, in step (2), after adding the cross-linking agent, stirring is carried out for hydrolysis, and the hydrolysis time is 1-2 hours. If the time is short, the silane coupling agent is not completely hydrolyzed, and if it is long, the cross-linking is too dense. After adding the catalyst, stirring is carried out for cross-linking, and the stirring time is 2.5-3.5 hours. If the stirring time is short, the cross-linking is not complete, and if it is long, the cross-linking is dense and cannot form the villus structure of the small intestine.
[0026] Wherein, in step (2), the carbon source is dissolved in water, and the mass of the water accounts for 94.5-96.8% of the mass of the entire system obtained in step (3).
[0027] Wherein, in step (4), the time of directional freeze drying is 48 to 54; the temperature is -55 to -60°C; and the directional freezing method is the directional freezing method commonly used in the prior art.
[0028] The above-mentioned bionic intestinal villus aerogel is used in thermal insulation materials, flame retardant materials and antibacterial materials.
[0029] Principle of the invention: The present invention is based on biomass PA molecules, using the six strongly negatively charged active phosphate groups on its surface and PEI (H + ) surface has a high cationic charge density, which can bind PEI (H + ) combined with the phosphate group of PA to successfully construct an environmentally friendly electrolyte ligand. Then, preferably with HPMC as the carbon source, MTMS as the crosslinker, and ammonia water as the catalyst, the bio-based electrolyte ligands with different PEI to PA mass ratios were grafted into the HPMC-MTMS system by in situ polymerization, and the HPMC-MTMS-PP biomimetic intestinal villus composite aerogel was successfully constructed. The results show that when the mass ratio of PEI to PA is 2:1 and 1:1, the electrostatic and hydrogen bonding between the ligands and the hydrogen bonding of the entire system reach a state of equilibrium, and the composite aerogel forms a biomimetic intestinal villus structure.
[0030] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:
[0031] (1) The present invention grafts the bio-based electrolyte phytic acid-polyethyleneimine ligand into an aerogel system with a layered structure formed by a carbon source, a crosslinking agent, and a catalyst by an in situ polymerization method, and successfully constructs a biomimetic intestinal villus type composite aerogel. While enhancing the flame retardancy (LOI can reach 30.2%, reaching the UL-94-V0 flame retardancy level, and the PHRR and THR can be reduced by up to 61.14% and 58.21%) and thermal insulation properties (thermal conductivity as low as 0.0319 W / (m·K)), the antibacterial properties of the material are also significantly improved (anti-Escherichia coli rate is 94.36%, and anti-Staphylococcus aureus rate is 82.10%).
[0032] (2) The product formula of the present invention is more environmentally friendly, the preparation process is simpler, and can be carried out at room temperature, thereby reducing energy consumption and increasing the high-value utilization of waste wood fibers.
[0033] (3) ① Optimization of flame retardant performance: In order to inhibit flame propagation and high-temperature oxidation, the formula of the present invention introduces an environmentally friendly flame retardant formed by a PA-PEI ligand with high-efficiency flame retardant function, and at the same time simulates the hierarchical porous structure of the small intestinal villi, and forms a heat barrier inside the aerogel through a multi-level pore layer, which not only prolongs the flame penetration time, but also protects the matrix structure by forming a carbon layer, further improving the flame retardant performance of the material. ② Improved antibacterial performance: The porous structure of the aerogel provides a potential living space for microorganisms. The formula of the present invention specifically adds phytic acid, a natural antibacterial ingredient, combined with the high surface area of the bionic structure of the small intestinal villi, to achieve a lasting antibacterial effect, which can effectively prevent bacteria and fungi from adhering and growing on the surface of the material, and prolong the application life of the aerogel. ⑤ Enhanced thermal insulation performance: In order to achieve efficient thermal insulation, the present invention adopts a bionic multi-level pore structure with a low thermal conductivity coefficient, so that the internal heat conduction path of the aerogel is significantly extended. At the same time, the three heat transfer modes of conduction, convection and radiation are effectively isolated through the hierarchical structure to achieve excellent thermal insulation effect. This material can maintain thermal stability under extreme environments and is suitable for high-efficiency thermal insulation applications in construction, industry, aerospace and other fields.
[0034] (4) In order to realize the bionic structure of the small intestinal villi, the present invention uses biomass electrolyte phytic acid-polyethyleneimine ligands and a special self-assembly process method to allow the material to naturally grow into a bionic porous structure in a hierarchical manner during the molding process. This process ensures the uniformity and stability of the villi structure by precisely controlling the proportion of the biomass ligands.
[0035] (5) The aerogel of the present invention can be applied to building partitions, fire-fighting equipment shells and high-temperature pipe insulation, and can provide excellent flame retardant protection under high temperature conditions such as fire; it can be applied to the lining of medical equipment, protective equipment, air purification equipment, etc. to prevent bacterial growth and reduce the risk of pollution, and meet the needs of long-term cleanliness and safety; it can be applied to the insulation layer of construction, aerospace and industrial equipment, providing lightweight and efficient insulation solutions, and providing thermal protection support for high-end equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The scanning electron microscope images of the aerogels of the embodiments and comparative examples are shown;
[0037] Figure 2 The flame retardant performance test results of the aerogels in various embodiments and comparative examples are shown in FIG.
[0038] Figure 3 The limiting oxygen index and effective combustion heat test results of the aerogels of various embodiments and comparative examples are shown in FIG.
[0039] Figure 4 It is a peak change diagram of the heat release rate of the aerogels of each embodiment and comparative example;
[0040] Figure 5 It is a comparison chart of the heat release rate and total heat release of the aerogels of various embodiments and comparative examples;
[0041] Figure 6 It is a comparison chart of the total smoke release and CO release peak of the aerogels in each embodiment and comparative example;
[0042] Figure 7 The carbon residue photographs of the aerogels of the embodiments and comparative examples are compared;
[0043] Figure 8 It is a comparison chart of thermal conductivity of aerogels in various embodiments and comparative examples;
[0044] Fig. 9 Schematic diagram of thermal insulation mechanism;
[0045] Fig.10 This is a comparison chart of the antibacterial effects of the composite aerogels of Examples 1 and 2 and Comparative Examples 2 and 3, and the pure HM aerogel of Comparative Example 1;
[0046] Fig.11 The pressure-strain curves of the composite aerogels of Examples 1 and 2 and Comparative Examples 2 and 3, and the pure HM aerogel of Comparative Example 1;
[0047] Fig.12 The figure is a comparison chart of the mechanical properties of several materials in the prior art and the aerogel obtained in Example 1. DETAILED DESCRIPTION
[0048] The present invention is described in further detail below.
[0049] Example 1
[0050] A bio-based electrolyte ligand-guided highly flame-retardant, antibacterial and heat-insulating bionic intestinal villus aerogel has a hierarchical porous structure, wherein the hierarchical porous structure comprises an aerogel skeleton with a layered structure, and each layer of the aerogel skeleton is uniformly grafted with a bionic villus structure; the bionic intestinal villus aerogel comprises the following components by mass: 1 part of a carbon source, 2 parts of a cross-linking agent, 0.5 parts of a catalyst, and 0.5 parts of a phytic acid-polyethyleneimine ligand; wherein the carbon source is hydroxypropyl methylcellulose, referred to as HPMC, type II, with a viscosity of 4000 mpa.s; the cross-linking agent is methyltrimethoxysilane, referred to as MTMS; and the catalyst is ammonia water.
[0051] The method for preparing the bionic intestinal villus aerogel comprises the following steps:
[0052] (1) At room temperature, 10 g of polyethyleneimine (hereinafter referred to as PEI) with a weight average molecular weight of 70,000 was dissolved in 40 g of deionized water, stirred at high speed for 5 min, and then continued to stir until the PEI was completely dissolved;
[0053] (2) After adding 15 ml of acetic acid to the completely dissolved PEI aqueous solution to adjust the pH to 3-4, the solution was stirred at a low speed for 0.5 h to complete the protonation, and then 20 g of a 50% phytic acid (PA) aqueous solution was added and stirred at a high speed to immediately generate a white precipitate; wherein the mass ratio of PEI to PA was 1:1;
[0054] (3) washing the precipitate using a vacuum filter, freezing the precipitate at -20°C for 8 hours and then freeze-drying it for 36 hours to obtain a bio-based electrolyte PEI-PA ligand;
[0055] (4) The bio-based electrolyte obtained by freeze drying was dried in an oven at 60°C for 8 h and then ground into powder for storage;
[0056] (5) At room temperature, dissolve HPMC in an appropriate amount of deionized water and stir at high speed until it is completely dissolved to form a transparent viscous liquid;
[0057] (6) Add MTMS to the dissolved HPMC aqueous solution and stir at high speed for 1.5 h;
[0058] (7) adding ammonia water as a catalyst and stirring at high speed for 3 h to form a light blue wet gel precursor; wherein;
[0059] (8) Add ligand powder and stir at high speed for 3 hours until the ligand is completely dissolved and dispersed in the entire wet gel precursor; wherein the mass percentages of HMPC, MTMS, ammonia water, and ligand powder respectively account for 1wt%, 2%, 0.5%, and 0.5% of the mass of the entire system obtained in step (8).
[0060] (9) In a liquid nitrogen environment at -196°C, the gel precursor obtained in step (8) was freeze-dried for 48 h using a directional freeze-drying method to obtain an aerogel sample, which was recorded as HM-PP (1:1).
[0061] Example 2
[0062] On the basis of Example 1, different from Example 1, the mass ratio of PEI to PA is 2:1, and the obtained aerogel is recorded as HM-PP (2:1).
[0063] Example 3
[0064] On the basis of Example 1, different from Example 1, in the whole system obtained in step (8), the mass proportion of HPMC is 1.5%, the mass proportion of MTMS is 2.5%, the mass proportion of ammonia water is 0.2%; and the mass proportion of ligand powder is 1%.
[0065] Comparative Example 1
[0066] Based on Example 1, the difference from Example 1 is that steps (1)-(4) and step (8) are omitted, that is, no ligand powder is added to the gel precursor to obtain pure HM aerogel.
[0067] Comparative Example 2
[0068] Based on Example 1, different from Example 1, the mass ratio of PEI to PA is 1:2.
[0069] Comparative Example 3
[0070] Based on Example 1, different from Example 1, the mass ratio of PEI to PA is 1:3.
[0071] Comparative Example 4
[0072] The mechanical properties of several materials in the prior art were compared with the aerogel obtained in Example 1. Fig.12 As shown; among them, Fig.12 The "CNC / MTMS" in comes from the literature: Bioinspired "aerogel grating" with metasurfaces for durable daytime radiative cooling for year-round energysavings, Chenyang Cai, etc. Nano Energy.
[0073] "CNF" comes from the literature: Defect reduction to enhance the mechanical strength of nanocellulose carbon aerogel, Haihong Lai, etc. Chinese Chemical Letters.
[0074] "MXene / NCF" comes from the literature: MXene / N-Doped Carbon Foam with Three-DimensionalHollow Neuron-like Architecture for Freestanding, Highly Compressible AllSolid-State Supercapacitors, Li Sun, etc.ACS Applied Materials&Interfaces.
[0075] "CNF / HTDMS" comes from the literature: Enhancing the Oil Adsorption Properties ofCellulose NanofiberAerogels Through Chemical Modification,Sara Sadat Fazel,etc.Journal ofPolymers and the Environment.
[0076] "Cellulose" comes from the literature: Aerogel nanoarchitectonics based on cellulosenanocrystals and nanofibers from eucalyptus pulp: preparation and comparative study, Wenkai Zhu, etc. Cellulose.
[0077] "Silylated CNF" comes from the literature: Ultralight, hydrophobic, anisotropic bamboo-derived cellulose nanofibrils aerogels with excellent shape recovery viafreeze-casting, Xuexia Zhang, etc. Carbohydrate Polymers.
[0078] "CNFs / CNC" comes from the literature: Rice straw agri-waste for water pollutantadsorption: Relevant mesoporous super hydrophobic cellulose aerogel, Mandana Dilamian, etc. Carbohydrate Polymers.
[0079] Comparative Example 5
[0080] Based on Example 1, the difference from Example 1 is that in step (6), the stirring time is 0.5 h. The cross-linked structure is uneven, and the aerogel is fragile and soft.
[0081] Comparative Example 6
[0082] Based on Example 1, the difference from Example 1 is that in step (7), the stirring time is 2 hours. The structure is soft and easy to collapse and break.
[0083] Figure 1 The electron microscope microstructures of several composite aerogels, where (a) is the pure HM aerogel prepared in comparative example 1, (b) is the aerogel obtained in Example 2, wherein the mass ratio of PEI to PA is 2:1; (c) is the aerogel obtained in Example 1, wherein the mass ratio of PEI to PA is 1:1; (d) is the aerogel obtained in comparative example 2, wherein the mass ratio of PEI to PA is 1:2; (e) is the aerogel obtained in comparative example 3, wherein the mass ratio of PEI to PA is 1:3. It can be seen that the pure HM aerogel exhibits a regular pore distribution and a uniform skeleton structure, while in the HM-PP (2:1) and HM-PP (1:1) composite aerogels ( Figure 1 ), bionic bifurcated villi structures appeared on the Si-OC skeleton formed by HPMC and MTMS. These villi structures were closely grafted on the layered framework of the composite aerogel and presented a multi-layer villi arrangement.
[0084] In PA and PEI (H + ) mass ratio is 2:1 and 1:1, the system reaches a certain equilibrium state, which is conducive to the formation of uniform and directional self-assembly behavior. This equilibrium state indicates that the electrostatic interaction between the two ratios of ligands is relatively weak. In the HM system, the hydrogen bonds and electrostatic interactions between the hydroxyl groups on the surface of HPMC and the Si-O-Si and Si-OC networks formed after the hydrolysis of MTMS, as well as between the ligands (amino and phosphate groups), compete with the electrostatic interaction of PP itself, so that the ligand structure can be evenly dispersed throughout the system, promoting the formation of an ordered, directional microstructure, and showing a villi-like appearance. In addition, the presence of HPMC provides the system with more polar groups and hydrogen bond donors / acceptors, which can react with PEI (H + ) and the functional groups of PA interact more effectively, reducing the aggregation tendency of the ligand in the system. At the same time, HPMC significantly increases the viscosity of the solution, which helps to stabilize the ligand particles dispersed in the system, prevents them from rapid sedimentation or aggregation, and makes the dissociation and dissolution process of the electrolyte ligand more controllable.
[0085] When the ratio of PP ligands is 1:2 or 1:3, this equilibrium state is broken, forming an irregular self-assembly pattern. Due to the high PA ratio, the network structure may become more dense and uniform, and the ligands tend to aggregate into a nano-spherical particle structure. This structure is more compact but lacks directionality, thus forming a spherical microstructure. In addition, during the freeze-drying process, the spherical aggregates of the ligands are difficult to align during the growth of ice crystals and ultimately remain as a spherical structure. Therefore, a higher PA content leads to a different self-assembly mode, which affects the formation of the final structure.
[0086] like Figure 2 , 3 , 4, and 5, the aerogel samples were subjected to vertical combustion (UL-94), limiting oxygen index (LOI), and cone calorimetry tests, and the microstructure of the carbon residue was as follows: Figure 7 As shown. Figure 3 As shown in the figure, the LOI of pure HM and HM-PP composite aerogels are 19.5%, 27.8%, 30.2%, 30.5% and 31.6% respectively. The bio-based electrolyte PP ligand in the composite aerogel has a significant inhibitory effect on the combustion of Si-O-Si and Si-OC in the HM skeleton, and the introduction of the ligand improves the composite aerogel to a flame retardant level. In addition, the aerogel sample is 35Kw / m 2 Under the radiation intensity of , the results of peak heat release rate (PHRR), heat release rate (HRR), total heat release (THR), effective heat of combustion (EHC), total smoke release (TSP) and peak CO release are as follows Figure 3 , 4 , 5, and 6. Figure 5 In the figure, the peak of the first stage represents the rapid formation of a carbon protective layer on the aerogel surface after the flame ignites the sample. As the temperature rises, the carbon layer breaks and a large amount of combustible molecules are released, forming the PHRR of the second stage. Compared with pure HM aerogel, the PHRR of HM-PP (2:1) and HM-PP (1:1) composite aerogels in the second stage can be reduced by up to about 21.92%. In addition, Figure 5 As shown in the figure, the PHRR and THR of the composite aerogel can be reduced by about 61.14% and 58.21% at most, while with the increase of the proportion of phytic acid in the PP ligand, the HRR and THR show a slightly enhanced phenomenon. Figure 3As shown in the figure, EHC represents the ratio of HRR to mass loss rate, which reflects the combustion rate of volatile gases in meteorological flames. As the PA in PP increases, more CO2 and water molecules are generated. Therefore, HM-PP (1:2) and HM-PP (1:3) composite aerogels show higher EHC, while HM-PP (2:1) and HM-PP (1:1) that reach system equilibrium have no more free PA molecules, thus forming a lower EHC, which can reach a minimum of 4.48MJ / kg. The EHC of pure HM is more than 10 times that of the composite aerogel, which is 51.02MJ / kg. In addition, during the combustion process, the TSP of pure HM and HM-PP composite aerogels showed a trend of first decreasing and then increasing, while the CO release showed a continuous decrease. Therefore, when the PP ligand ratio is 2:1 and 1:1, the char layer after ignition forms the most compact structure, which effectively inhibits the combustion of combustible molecules and minimizes the release of TSP and CO, ultimately showing the lowest HRR and THR. Figure 7 It can also be observed that compared with the weak carbon residue structure of pure HM aerogel, the carbon residues of HM-PP (1:2) and HM-PP (1:3) deform and form voids in the middle, while the carbon layer structure of HM-PP (2:1) and HM-PP (1:1) shows a relatively complete and dense structure. This is precisely because too much PA causes more CO2 and water molecules to be generated. If a large amount of gas is quickly released and trapped in the carbon layer, it may expand at high temperature, causing the local carbon layer to rupture or separate, and finally form voids.
[0087] like Figure 8 As shown in Figure 2, the thermal conductivity of HM aerogel is as low as 0.0344 W / (m 2 ·K), the thermal conductivity of HM-PP composite aerogels with different ratios of ligands decreased slightly. The average thermal conductivity of HM-PP (2:1), HM-PP (1:1), HM-PP (1:2) and HM-PP (1:3) composite aerogels were 0.0280, 0.0275, 0.0305 and 0.0315 W / (m 2 On the one hand, the bionic villi structure formed by HM-PP (2:1) and HM-PP (1:1) increases the specific surface area of the composite aerogel, further increases the heat transfer path, and enhances the air capture capacity inside the aerogel. As a good insulator, air can effectively prevent heat conduction, such as Fig. 9On the other hand, since thermal convection is an important mechanism for heat transfer inside the gas, limiting convection can help further improve the thermal insulation performance of the material. The bionic velvet structure can effectively limit the flow of air inside the material and effectively inhibit the occurrence of thermal convection.
[0088] like Fig.10 As shown in the figure, pure HM aerogel has different antibacterial effects on Escherichia coli and Staphylococcus aureus. For Gram-negative Escherichia coli, pure HM aerogel has almost no antibacterial activity, while composite aerogels with different proportions of PP ligands all produce inhibition zones of different sizes, which decrease with the increase of the proportion of PA in the ligand. Among them, when the weight ratio of PEI to PA in the ligand is 2:1, the PA in the ligand is in the PEI (HM) + ) still has vacant positions on the active sites. In this process, PEI(H + ) enhanced the overall antibacterial effect of the composite aerogel and formed the largest inhibition zone. For Gram-positive Staphylococcus aureus, pure HM aerogel produced the greatest antibacterial effect, and as the proportion of PA in the ligand increased, the antibacterial effect weakened. The inhibition zones of HM-PP (2:1), HM-PP (1:1), HM-PP (1:2) and HM-PP (1:3) composite aerogels were 26, 19, 17 and 13 mm, respectively. The diameters of the largest inhibition zones formed by the composite aerogel against Escherichia coli and Staphylococcus aureus were 26 mm and 20 mm, and overall, the antibacterial effect of the composite aerogel against Escherichia coli was slightly stronger than that against Staphylococcus aureus.
[0089] The OD value can quantitatively evaluate the antibacterial rate of the composite material. The activated Escherichia coli and Staphylococcus aureus were treated with LB broth and the concentration of the bacterial suspension was further controlled by measuring the OD value (recorded as the total bacterial count) to maximize the uniformity of each test sample (5 tests were recorded as the average value). 1 ml of the composite aerogel precursor liquid was added to the bacterial suspension and shaken at 37 ° C for 12 hours. The antibacterial rate was calculated by OD value test and formula (1) as shown in Table 1. It can be found that with the increase of the proportion of PA in the ligand, the antibacterial rate of the composite gel against Escherichia coli decreased from a maximum of 94.36% to a minimum of 47.98%. For Staphylococcus aureus, a similar law of decreasing antibacterial effect was also produced, with the highest and lowest being 82.10% and 35.63%.
[0090] Antibacterial rate calculation formula:
[0091]
[0092] Note: OD b and OD ais the optical density of the bacterial suspension before and after adding the aerogel sample.
[0093] Table 1
[0094]
[0095]
[0096] In order to further understand the antibacterial mechanism of the ligand composite aerogel, the microstructure of bacteria (Escherichia coli and Staphylococcus aureus) after 12h incubation was analyzed by SEM. Fig.10 As shown in the figure, the cell membrane structure of E. coli in the pure HM aerogel bacterial suspension is intact and the cells are full of activity, while in the bacterial suspension incubated with HM-PP composite aerogel, some bacterial cell membranes show rupture, tearing and leakage of contents. On the one hand, this is due to the PEI (H + ) is a positively charged cation, which interacts with the negatively charged bacterial cell membrane surface. This electrostatic interaction causes the bacterial cell wall to rupture, resulting in leakage of cell contents, thus producing antibacterial properties. On the other hand, PA and PEI (H + )'s chelation will have an inhibitory effect on bacterial metabolism, and the multiple effects of PEI's large molecular weight and cationic strength coordinate with each other, making the hybrid body have better stability, and it is possible to achieve sustained release of antibacterial components and prolong the duration of antibacterial effect. Therefore, the bionic composite aerogel exhibits excellent anti-E. coli performance. The cell membrane of Staphylococcus aureus in the pure HM aerogel bacterial suspension showed rupture, tearing and even leakage of contents, while the effect of cell destruction in the bacterial suspension of the composite aerogel with the addition of ligand PP showed a decreasing effect. With the increase of PA in the ligand, PEI (H + ) and the cell membrane of Staphylococcus aureus are competitively affected by the phosphate groups, and this competitive effect produces a weakening effect, which is consistent with the test results of the OD value. In addition, the siloxane network formed by MTMS on the surface of the material is hydrophobic and chemically inert, which can destroy the integrity of the bacterial cell wall or membrane and inhibit the attachment and reproduction of bacteria. In summary, HM-PP (2:1) exhibits excellent performance against Escherichia coli and Staphylococcus aureus.
[0097] like Fig.11As shown in the figure, the pressure-strain curves of pure HM aerogel and HM-PP composite aerogel were further studied. It can be seen that the compressive stress of pure HM aerogel is the lowest at 80% strain, which is about 20.63KPa. With the increase of PA ratio, the compressive strength of PP ligand hybrid aerogel first increases and then decreases, and the maximum compressive strength is about 126.21KPa (HM-PP (1:1)). This shows that the strain resistance given to the matrix by the villi structure is more uniform in the vertical direction, thus showing a considerable compressive effect, which has certain advantages compared with previous studies, such as Fig.12 However, the irregular spherical aggregates make the internal stress of the material less concentrated, resulting in a decrease in compressive stress.
[0098] The relevant testing standards and processes of the present invention are as follows:
[0099] 1. Flame retardant test of aerogel:
[0100] According to the UL-94 vertical burning rating test standard steps of GBT2408-2021:
[0101] ① Equipment preparation: The sample size generally requires the sample thickness to be between 0.1mm and 12.7mm, usually 125mm long x 13mm wide. Flame source: Use a suitable burner to produce a 40±2mm blue flame. Combustion environment: Test in a windless closed combustion box to ensure a stable environment.
[0102] ② Sample fixation: The top of the sample is fixed on the fixture and hung vertically in the combustion chamber. Cotton or absorbent paper is placed under the sample to observe whether there are any molten droplets falling.
[0103] ③ Vertical combustion test steps: First ignition: bring the flame close to the bottom of the sample, 10mm away from the sample, ignite, and set the burning time to 10 seconds. After the flame is removed, start recording the sample's self-ignition time and observe whether the flame can automatically extinguish. Record the extinguishing time and observe whether there are burning drips. If there are drips, record whether they ignite the cotton below. Second ignition: If the sample extinguishes after the first combustion, immediately bring the flame close to the bottom of the sample again and continue burning for 10 seconds. Also record the extinguishing time and dripping.
[0104] ④Observation and recording: Record the self-extinguishing time and dripping conditions of the sample after two ignitions, and observe whether the sample meets the requirements of the corresponding level in the UL-94 standard. Rating is based on the characteristics of the sample in the test:
[0105] V-0: The sample can self-extinguish within 10 seconds in both combustions, and there is no dripping of cotton ignition.
[0106] V-1: The sample can self-extinguish within 30 seconds in both combustions, and there is no dripping of cotton ignition.
[0107] V-2: The sample can self-extinguish within 30 seconds in both combustions, but there are drippings that ignite the cotton.
[0108] ⑤ Analysis and determination: Based on the recorded burning time, dripping behavior and self-extinguishing condition, determine whether the flame retardant grade of the sample meets the grade requirements of UL-94 V-0, V-1 or V-2. The results are as follows: Figure 2 .
[0109] According to GB2406-80 and ASTM D2863 limiting oxygen index test standards:
[0110] ①LOI tester: usually a vertical combustion column, with different concentrations of oxygen-nitrogen mixed gas flow inside to control the oxygen content. Sample size: according to the test standard, it is usually necessary to cut into sample strips of 80mm long x 10mm wide x 4mm thick.
[0111] ② Set the initial oxygen concentration: Set the oxygen concentration in the airflow to an initial value, such as between 21-25%, and then gradually adjust it to find the minimum oxygen concentration at which the material can continue to burn.
[0112] ③ Ignite the sample: Fix the sample vertically in the combustion column and ignite the upper end of the sample. Usually use a small flame to ignite for 3 to 5 seconds, and then remove the fire source.
[0113] ④Adjust oxygen concentration: observe the combustion of the sample and adjust the oxygen concentration
[0114] ⑤ Record LOI: LOI<21%: The material is flammable and has poor flame retardancy. 21%<LOI<26%: The material has average flame retardancy. LOI>26%: The material has good flame retardancy. LOI>32%: The material has strong flame retardancy and is mostly used in occasions with special fire protection requirements, such as Figure 3 shown.
[0115] According to GB / T16172-2007 cone calorimetry test standard test equipment preparation:
[0116] ① Cone calorimeter test: Cone calorimeter is usually used, and its main components include: Sample tray: used to place the sample to be tested. Oxygen / nitrogen gas mixture flow: provides oxygen to the sample and maintains the atmosphere required by the fire source. Fire source: a predetermined flame (usually 35kW / m 2 radiant heat source). Temperature sensor: used to monitor the surface temperature of the sample and the heat release in the test chamber.
[0117] ②Sample preparation: The sample size is based on the test standard requirements. Generally, a square sample of 10cm x 10cm is required, and the thickness is usually 2-5mm. The sample should be as flat as possible, with no dirt or impurities on the surface.
[0118] ③Install the sample: Fix the sample on the sample tray of the cone calorimeter. Make sure the sample surface is consistent with the radiation surface of the fire source so that the material surface can be evenly heated during the test.
[0119] ④Test process: Start the instrument and set a suitable radiation heat source, usually 50kW / m 2 , to simulate the actual fire environment of the material. Ignite the sample and record the heat release rate (HRR), total heat release (THR), smoke production rate (SPR), CO and CO2 release, etc. during the combustion process. Measure and record parameters such as sample surface temperature, heat release rate, burning time, oxygen consumption, etc.
[0120] ⑤Data analysis: Heat release rate (HRR): HRR is the rate of heat released when a material burns, in kW / m 2 It reflects the burning intensity of the material. The higher the value, the more heat the material releases when burning. Total heat release (THR): is the sum of the heat released by the burning sample per unit time. This value can reflect the scale of the fire of the material. Smoke generation rate (SPR): refers to the amount of smoke generated per unit time, usually in m 2 / s. A high SPR value indicates that a large amount of smoke will be produced during the combustion of the material. Flame spread speed (TSP): The speed at which the flame spreads along the surface of the material, usually used to evaluate the speed of fire spread.
[0121] 2. Test steps for antibacterial samples:
[0122] ① Preparation of aerogel samples: Use scissors to cut the samples into discs with a diameter of 10 mm ± 0.5 mm, and sterilize the samples using ultraviolet irradiation.
[0123] ② Activation of bacteria: Mix LB agar with pure water in a certain ratio and place in a 121° high pressure sterilizer for 15 minutes, then pour the agar nutrient solution into the culture dish to solidify. Use an inoculation loop to inoculate E. coli and S. aureus into the culture dish respectively, and culture in a constant temperature and humidity incubator at 37°C and 60% for 24 hours.
[0124] ③ Rejuvenation of bacteria: Then, the activated strains were mixed with LB broth and pure water in a certain proportion and placed in a 121° high pressure sterilizer for 15 minutes, and then the broth nutrient solution was poured into the culture dish to solidify. Use an inoculation loop to inoculate the activated E. coli and S. aureus into the culture dish respectively, and culture on a shaker at 37°C for 24 hours. This process is the rejuvenation process of bacteria.
[0125] ④Prepare bacterial suspension: dilute the cultured bacteria with sterile water to an appropriate concentration, generally around 10^8 CFU / mL.
[0126] Spreading bacterial suspension: Pour the prepared agar medium into a sterile culture dish and wait for it to solidify. Then use a sterile spreading rod or glass rod to evenly spread the diluted bacterial suspension on the surface of the agar medium.
[0127] ⑤Placing aerogel: Carefully place the sterilized aerogel sample on the surface of the agar medium coated with bacterial solution to ensure good contact between the sample and the surface of the medium.
[0128] ⑥ Sample incubation: Place the inoculated culture dish in a 37°C incubator for 24-48 hours. Observe the inhibition zone: Observe whether an inhibition zone, i.e., a sterile growth zone, is formed around the aerogel sample. Use a ruler to measure the diameter of the inhibition zone in millimeters and record the measurement results. Fig.10 .
[0129] ⑦ Evaluate the antibacterial properties of the aerogel samples based on the diameter of the inhibition zone and compare the diameter of the inhibition zone with that of the control group (samples without antibacterial treatment) to determine the significance of the antibacterial effect.
[0130] Calculation of antibacterial rate: OD value of the control group - OD value of the experimental group / OD value of the control group * 100%. The results are shown in Table 1.
Claims
1. A bionic intestinal villus aerogel, characterized in that: It comprises an aerogel skeleton with a layered structure, on which a bionic villus structure is grafted; the bionic intestinal villus aerogel comprises the following components by mass: 1-1.5 parts of a carbon source, 1.5-2.5 parts of a crosslinking agent, 0.2-0.5 parts of a catalyst, and 0.5-1 parts of a phytic acid-polyethyleneimine ligand.
2. The bionic intestinal villus aerogel according to claim 1, characterized in that: The phytic acid-polyethyleneimine ligand is prepared by the following process: adjusting the aqueous solution of polyethyleneimine to be acidic, adding the phytic acid aqueous solution, stirring to generate a white precipitate, washing, freeze-drying, and obtaining the phytic acid-polyethyleneimine ligand; the mass ratio of the polyethyleneimine to the phytic acid is 1:1 to 2:
1.
3. The bionic intestinal villus aerogel according to claim 1, characterized in that: The carbon source is at least one of hydroxypropyl methylcellulose, cellulose nanocrystals or cellulose nanofibers; the crosslinking agent is methyltrimethoxysilane and / or hexadecyltrimethoxysilane; and the catalyst is ammonia water and / or sodium hydroxide.
4. A method for preparing the bionic intestinal villus aerogel according to claim 1, characterized in that: The following steps are involved: (1) adjusting the aqueous solution of polyethyleneimine ligand to be acidic, adding phytic acid aqueous solution, stirring to generate white precipitate, washing, freeze-drying to obtain phytic acid-polyethyleneimine ligand, and grinding to obtain phytic acid-polyethyleneimine ligand powder; (2) dissolving the carbon source, adding a cross-linking agent to hydrolyze the carbon source to form a Si-O-Si network; then adding a catalyst to cross-link the carbon source and the cross-linking agent to form a gel precursor; (3) adding phytic acid-polyethyleneimine ligand powder to the gel precursor and stirring until the phytic acid-polyethyleneimine ligand is dissolved and dispersed in the gel precursor; (4) Directional freeze drying is performed to obtain bionic intestinal villus aerogel.
5. The method for preparing the bionic intestinal villus aerogel according to claim 4, characterized in that: In step (1), the mass ratio of polyethyleneimine to phytic acid is 1:1 to 2:
1.
6. The method for preparing the bionic intestinal villus aerogel according to claim 4, characterized in that: In step (1), the molecular weight of the polyethyleneimine is 70000-250000 M.W.
7. The method for preparing the bionic intestinal villus aerogel according to claim 4, characterized in that: The masses of the carbon source, cross-linking agent, catalyst and phytic acid-polyethyleneimine ligand powder account for 1-1.5%, 1.5-2.5%, 0.2-0.5% and 0.5-1% of the mass of the entire system obtained in step (3), respectively.
8. The method for preparing the bionic intestinal villus aerogel according to claim 4, characterized in that: In step (2), the stirring time after adding the cross-linking agent is 1-2 hours; the stirring time after adding the catalyst is 2.5-3.5 hours.
9. The method for preparing the bionic intestinal villus aerogel according to claim 4, characterized in that: In step (1), the aqueous solution of the polyethyleneimine ligand is adjusted to a pH value of 3-4.
10. Use of the bionic intestinal villus aerogel according to claim 1 in thermal insulation materials, flame retardant materials and antibacterial materials.
Citation Information
Patent Citations
Humic acid type antibacterial slow-release herbicide and preparation method thereof
CN115316398A
Preparation method of flame-retardant material based on graphene oxide
CN116334913A
Preparation method of modified nano cellulose
CN118388775A
Functional chitosan-based composite aerogel as well as preparation method and application thereof
CN118634792A
Microfibrillated lignocellulose foams and methods to prepare them
WO2024011309A1